2009
DOI: 10.1186/1475-2875-8-203
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of artesunate-amodiaquine for treating uncomplicated falciparum malaria in sub-Saharan Africa: a multi-centre analysis

Abstract: Background: Artesunate and amodiaquine (AS&AQ) is at present the world's second most widely used artemisinin-based combination therapy (ACT). It was necessary to evaluate the efficacy of ACT, recently adopted by the World Health Organization (WHO) and deployed over 80 countries, in order to make an evidence-based drug policy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
54
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 77 publications
(68 citation statements)
references
References 45 publications
(48 reference statements)
13
54
1
Order By: Relevance
“…This significant fever clearance difference for the comparison of AS+AQ and AL have also been reported by Koram et al (p=0.006) 32 . In this report, the proportion of patients treated with AS+AQ that remained febrile at Day 2 was significantly lower when compared to those treated with AL, similar to a finding previously reported in another larger study (2.8% versus 6.3%, respectively; p=0.001) 14 . Even though the clinical relevance of small but significant differences in fever clearance times is arguable, it seems evident that ACT in general 26 , and AS+AQ in particular, offer a faster relief from the febrile state and the associated inflammatory response.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…This significant fever clearance difference for the comparison of AS+AQ and AL have also been reported by Koram et al (p=0.006) 32 . In this report, the proportion of patients treated with AS+AQ that remained febrile at Day 2 was significantly lower when compared to those treated with AL, similar to a finding previously reported in another larger study (2.8% versus 6.3%, respectively; p=0.001) 14 . Even though the clinical relevance of small but significant differences in fever clearance times is arguable, it seems evident that ACT in general 26 , and AS+AQ in particular, offer a faster relief from the febrile state and the associated inflammatory response.…”
Section: Discussionsupporting
confidence: 91%
“…The correlation between parasitemia and fever clearance times has been verified in other reports 14,33 . The study by Zwang et al found that parasitemia and fever percentages of patients treated with AS+AQ were, respectively, 66.4% and 7.4% on day 1; 8.5% and 2.4% on day 2; 1.8% and 2.4% on day 3; and 0.6% on day 7.…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations